Recent developments of atmospheric research in Ukraine - Milinevsky, G.P.; Danylevsky, V.O.; Grytsai, A.V.; Evtushevsky, O.M.; Kravchenko, V.O.; Bovchaliuk, A.P.; Bovchaliuk, V.P.; Sosonkin, M.G.; Goloub, Ph.; Savitska, L.Y.; Udodov, E.V.; Voytenko, V.P. (Advances in Astronomy and Space Physics, 2012)
In recent years the Joint Laboratory of Atmospheric Optics and Aerosols of Ukraine has been carrying out atmospheric research in cooperation with international program of climate change studies. Our current research is aimed at studying aerosol and ozone in the Earth's atmosphere, because these constituents have a substantial inадuence on climate. In Ukraine, atmospheric aerosol remote sensing in the PHOTONS/AERONET network has been carried out since 2006 in Sevastopol and 2008 in Kyiv. For this research, sunphotometers CIMEL CE318 have been used. A mobile AERONET station has been developed, which consists of CE318N and portable Microtops II sunphotometers, as well as two self-designed experimental portable sunphotometer models and an ozonometer for aerosol and ozone study. The team's findings on aerosol spectral optical thickness, as well as optical and physical properties of aerosol particles (single-scattering albedo, distribution of particles by sizes, Ångström exponent), are discussed in the paper. In 2010, upon the establishment of the new regional atmospheric research station Nr. 498 Kyiv-Goloseyev, the team commenced with measurements of the total column density and vertical distribution of ozone, using the Dobson D040 spectrophotometer, in the framework of the Global Atmosphere Watch Program of WMO. The station has also been equipped with a Vaisala automatic weather station, a surface ozone 49i analyzer, and an experimental complex for monitoring secondary space rays. The aerosol and ozone measurements have been continuously submitted to data centres of AERONET (http://aeronet.gsfc.nasa.gov/) and WMO (www.woudc.org/data/). For aerosol and ozone research, the data from satellite sources (POLDER, MODIS, OMI, and SCIAMACHY) have also been analysed. The work on a proposal to design, build, and launch the space radiometer/polarimeter for global monitoring of atmospheric aerosols has commenced recently. This instrument should have the capability of investigating microphysical properties of aerosol particles. An overview of the devices, methods of data retrieval analysis of aerosol parameters and ozone dynamics, is presented in this paper.